Economic impact and growth rate of Red Sokoto goats fed treated municipal organic waste and grass/legume mixtures - Anigbogu, N.M.; Agida, C. A.; Chukwurah, C. B.; Afam-Ibezim, E. M.; Efuribe, B.E. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
An experiment was carried out to determine the performance of Red Sokoto goats fed municipal organic waste (MOW) treated with diastic microbes. Eighteen (18) Red Sokoto goats with an average body weight of 8.01±2.50kg, were used in the study which was randomized into 3 groups of 6 goats per dietary group that replicated 6 times. Each group was assigned to one of the 3 diets as follows: Diet A = 45% Untreated Municipal organic waste; Diet B = 45% Treated municipal organic waste; and Diet C = 70% Treated municipal organic solid waste, while palm kernel cake, wheat offal, and molasses were used to balance the diets as formulated for the experiment. Each group was given diets that comprised of hay 0.5kg/head of mixed 3 parts Panicum maximum and 1 part Centrosema pubescens and concentrate ration mixture containing treated or untreated MOW, were offered daily, separately at 7:30am and 4:30pm, respectively. The goats were fed ad-libitum and clean water provided. They were weighed at the beginning of the study and at weekly intervals for 52 days. Feed was measured before giving to the animals for data collection. As noted on the average daily weight gain, feed intake and efficiency of feed utilization respectively, while the average daily concentrate and forage intakes revealed (p>0.05). There is (p<0.05 and p<0.01) respectively as noted on the cost benefit analysis measured, except on the cost of production that revealed (p>0.05). As noted in this study, the MOW when treated with diastic microbes could be used as part of compounded diets for goats at 45% to 70%, respectively. Therefore, it is recommended that, MOW which is in abundant in Nigeria be treated with diastic microbes and fed to goats at 45% to 70% as part of the formulated diets, and on 0.5kg/head of mixed 3 parts Panicum maximum and 1 part Centrosema pubescen.